2020
DOI: 10.1177/0306624x20967934
|View full text |Cite
|
Sign up to set email alerts
|

What if They Are All High-Risk for Attrition? Correlates of Retention in a Longitudinal Study of Reentry from Prison

Abstract: Longitudinal data are essential to research in criminology and criminal justice. Despite attrition’s implications for validity, understanding its sources is underexplored empirically. We examine the correlates of retention using covariates organized into domains of prediction, prevention, and projection. Data from the LoneStar Project, a three-wave longitudinal reentry study of 802 males recently released from prisoners in Texas, were analyzed to examine the correlates of proximal, distal, and any study retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Overall, 532 interviews were completed at Wave 2, and 505 interviews were completed at Wave 3, leaving a 69.3% and 65.3% retention rate, respectively. Including the 611 respondents who completed at least one follow‐up interview, the LoneStar Project's overall retention rate was 79.1% (Clark et al., 2020). Prior research using LoneStar Project data has demonstrated that listwise deletion of cases produces the most consistent findings in terms of accounting for attrition‐induced selection bias.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, 532 interviews were completed at Wave 2, and 505 interviews were completed at Wave 3, leaving a 69.3% and 65.3% retention rate, respectively. Including the 611 respondents who completed at least one follow‐up interview, the LoneStar Project's overall retention rate was 79.1% (Clark et al., 2020). Prior research using LoneStar Project data has demonstrated that listwise deletion of cases produces the most consistent findings in terms of accounting for attrition‐induced selection bias.…”
Section: Methodsmentioning
confidence: 99%
“…The SVORI project experienced substantial attrition between waves 1 and 2: only 60% of the initial wave 1 sample was retained in wave 2 (Lattimore et al, 2004). Large amounts of attrition are common (though not universal; see Clark et al, 2020; Fahmy et al, 2019; Mitchell et al, 2021) and other panel studies of formerly incarcerated individuals have also experienced substantial attrition (Western & Wildeman, 2009). Utilizing a similar approach to post-stratification weighting used by Wallace and Wang (2020) and Wallace et al (2020), we began by identifying which characteristics of respondents would be related to the employment outcome to construct our weights.…”
Section: Methodsmentioning
confidence: 99%
“…While our attrition rate is on par with prisoner reentry studies, it raises concerns of biased results, as respondents who were retained may differ from those who attrited. We have demonstrated in prior work that age, incarceration length, baseline honesty, and study commitment were positively associated with wave 3 retention, while gang membership, rearrest, and extrinsic motivations for study participation were negatively associated with retention [ 57 ]. We supplement those results by comparing retained ( N = 514) and attrited ( N = 288) respondents across the baseline measures derived from the activism and radicalism intentions scale (including reference group and item measures, described below).…”
Section: Methodsmentioning
confidence: 99%